Rancang Bangun Media Pembelajaran Interaktif Berbasis Augmented Reality pada Mata Pelajaran Dasar Dasar Teknik Elektronika - Yudi Hermansyah; Mahesi Agni Zaus (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
This study aims to design and develop an interactive learning medium based on Augmented Reality (AR) for the subject of Basic Electronics Engineering, particularly on the topic of active and passive electronic components, in order to enhance the understanding and learning motivation of tenth-grade students at SMK Negeri 5 Padang. The development method used is the Multimedia Development Life Cycle (MDLC), which includes the stages of conceptualization, design, material collection, production, testing, and distribution. The final product of this research is an Android application utilizing AR technology to display 3D objects of electronic components, equipped with learning materials, educational videos, interactive evaluations, and a scan marker feature. The results of the development and implementation of this learning medium show that the Android application serves as an interactive medium that supports the learning process through Augmented Reality technology. The application received a score of 93% from the Media Expert, categorized as “Valid,” and 89.3% from the Material Expert, also categorized as “Valid.” Furthermore, the practicality test conducted with students showed an overall score of 93.15%, categorized as “Very Practical.” Based on the design results and validation by the Media Expert and Material Expert, it can be concluded that this interactive learning medium based on Augmented Reality technology is highly feasible for use. Furthermore, the implementation of this application in the learning process shows an increase in student participation and enthusiasm during the learning activities. Students appear more interested in exploring the material through 3D visualizations provided by AR technology, compared to conventional methods. The interactivity offered by the application, such as evaluation features and educational videos, also helps students understand concepts in a deeper and more enjoyable way. This shows that the integration of AR technology in learning media not only improves the effectiveness of the quality of the material.